Status and influence of parental rearing style and social psychology process on social adaptability of medical students: using college students in Jilin Province, China, as an example - Du, Juan; Ge, Hongjuan; Nie, Wei; Feng, Xinrui; Shao, Bing (Frontiers in Psychology, 2025)
BackgroundAlthough social adaptability is crucial for medical students, the combined influence of parental rearing styles and social psychology process on this competency is not well-explored, particularly in the context of China. This study examines their status and relationships among Chinese medical students.MethodsAn online questionnaire survey based on the web-based survey platform “Questionnaire Star” was performed with medical college students in Jilin Province, China. The questionnaire content comprised the status of the participants' parental rearing style, social avoidance and distress, and social adaptability by employing specific survey scales, and mediation effect analysis was conducted to examine the mediating role of social psychology process in the relationship between parental rearing styles and social adaptability.ResultsTwo thousand hundred and sixty-six medical college students were subjected to statistical analysis. Parental rearing styles and social avoidance and distress show differences among sociodemographic factors of gender, household registration, whether is one-child, and parental education (p < 0.05). Students from urban households, with one-child identities and those whose parents had high educational levels obtained high social adaptability scores (p < 0.05). The multivariate analysis results are as follows: social distress (β = −0.399, p < 0.001), social avoidance (β = −0.304, p < 0.001), mother's rearing style of “emotional warmth and understanding” (β = 0.135, p < 0.001), and father's rearing style of “overprotection” (β = −0.087, p < 0.001) are the independent factors influencing medical college students' social adaptability. Mediation effect analysis further reveal that parental rearing styles of “emotional warmth and understanding” and “overprotective” can directly or indirectly affect students' social avoidance and distress to influence their social adaptability.ConclusionReducing students' social avoidance and distress, strengthening “emotional warmth and understanding,” and preventing “overprotective” parental rearing styles are effective ways to improve medical college students' social adaptability.